LASERPITIUM LATIFOLIUM ELEMENTAL COMPOSITION - Сікорин, У. Б.; Грицик, А. Р. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Laserpitium latifolium elemental studying was carried out by atomic adsorption spectroscopy method. We studied the iron, magnesium, zinc, manganese, cobalt, copper, lithium, chrome, cadmium, contents in the underground and overground parts of the plants. It was found that the contents of microelements in the overground part exceeds their contents in the underground part.